2019
DOI: 10.2147/idr.s226072
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Diversity of Virulence Genes in Multidrug Resistant <em>Escherichia coli</em> from a Hospital in Western China</p>

Abstract: BackgroundEscherichia coli strains are the most commonly isolated bacteria in hospitals. The normally harmless commensal E. coli can become a highly adapted pathogen, capable of causing various diseases both in healthy and immunocompromised individuals, by acquiring a combination of mobile genetic elements. Our aim was to characterize E. coli strains from a hospital in western China to determine their virulence and antimicrobial resistance potential.MethodsA total of 97 E. coli clinical isolates were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
2
1
0
Order By: Relevance
“…The isolated DEC pathotypes showed high resistance rates to Ampicillin agreement with another study had been reported high resistance in studies done by Li et al, (2019), Abbasi et al, (2020) and Hussein (2016). while there was no resistance for Piperacillin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The isolated DEC pathotypes showed high resistance rates to Ampicillin agreement with another study had been reported high resistance in studies done by Li et al, (2019), Abbasi et al, (2020) and Hussein (2016). while there was no resistance for Piperacillin.…”
Section: Discussionsupporting
confidence: 91%
“…High rate of resistance were recorded for amikacin was agreement with studies of Abdulkareem (2016) and Jameel (2014) was 92%, 70%, respectively, while in Li et al ( 2019), Abdul-hussein et al (2018 and Hussein (2016) low resistance were 8.25%, 7.1% and 3.3% respectively .…”
Section: Discussionsupporting
confidence: 89%
“…The higher resistance rates against several antimicrobials of E. coli isolated from hospitals were observed in 2017 and 2018 ( 17 , 18 ). The first-line AMR rates of E. coli from western China were higher than those in eastern China ( 19 , 20 ). However, there are limited systematic monitoring reports about the animal origin of resistant bacteria, and most studies surveyed a few regions randomly and without genomic characterization ( 15 ).…”
Section: Introductionmentioning
confidence: 83%